Students' Perception of the Use of Technology in Education - Nur Zaimah, Ubaidillah; Nur Nadhira, Baharuddin; Nurizwani, Kasil; Farhana, Ismail (e-International Publishing House, Ltd., UK., 2020)
The changes that happen in technology recently have brought about significant changes in the field of education where it can improve the quality of knowledge with the invention of technology is creative, unique, and of course, it is beneficial to us especially among students. There is a growing number of interests in how these technological platforms are perceived by the users (students) and the effectiveness of these platforms. For this reason, it is essential to investigate the easiness and usefulness of such technology being currently used by students. To further understand the issue, the role of students' perception plays an essential role in the use of technology in education. Therefore, this study focuses on the students' understanding of the use of technology in learning among students at the University Malaysia Sarawak (UNIMAS) by applying the Technology Acceptance Model (TAM). Besides, this is an exploratory study on the impact of TAM on students' perception. An online questionnaire has been distributed, and a total of 113 respondents were collected, which aims to gather insight on the use of technology in the learning system at UNIMAS. Moreover, this study has used various analysis methods such as descriptive analysis, reliability test, factor analysis, and Pearson correlation coefficient and Partial Least Square- Structural Equation Model (PLS-SEM) to investigate the role of perceived ease of use and perceived usefulness in determining the usage of technology in the higher learning institution. The findings in this study revealed that there is a positive relationship from perceived ease of use towards the use of technology among students. The outcome of the study identifies that there is a satisfactory level of technology usage among the respondents. The results also suggest that policymakers should ensure the innovation of technology to consider the ease of use and usefulness of technology (via training and providing mobile-friendly applications) to assist students' learning in the higher learning institution. The limitations of this study are that the sample is collected at the undergraduate level. It is recommended for future research to include respondents from postgraduate levels to see any difference in their perception of technology.